OVERVIEW OF FINANCIAL TECHNOLOGY IN BANKING SECTOR: A BIBLIOMETRIC STUDY - Alfiana Nur Fadhilah; An Nurrahmawati (Universitas Tidar, 2024)
This study aims to provide empirical evidence regarding the growth and trend of fintech-related publications in the banking sector and examine what variables are often associated with fintech. Utilizing bibliometric analysis via the VOSviewer application, this study analyzes 816 articles published on Scopus from 2013 to 2023. The results of this study indicate that research publications on fintech in the banking sector have been widely carried out in various countries. Several variables related to fintech and banking topics include technology, industry, covid, future, and blockchain. Some of the authors that are widely found are M.K. Hassan, H. Banna, and M.R. Rabbani which can be considered as references. The study's limitation lies in its inability to provide an overview of variable usage trends in 2023. This research is expected to provide implications for the development of future research, especially related to fintech and banking.